Examination of the reasons for preferring tennis by the athletes participating in the Eastern League tennis tournament (Revista de Investigaciones Universidad del Quindío, 2022)
This research was conducted to determine the reasons and expectations of tennis players participating in the Eastern League organized by the tennis federation, preferring this sports branch. The research group consists of 138 athletes (53 women and 85 men) participating in the Eastern League Tennis Tournament. The scanning method was used in the research. As a data collection tool, a personal information form prepared by taking expert opinions and a scale form determining the reasons for preferring the tennis branch were used. SPSS statistical package program was used to analyze the data, and the significance was accepted as p
Keywords: Tennis; Eastern League; Expectations; tennis players; sports